Geotouristic attractions of the Klyuchevskoy group volcanoes, North Kamchatka, Russia - Łodziński, Marek (Geotourism/Geoturystyka, 2025)
The paper describes the geotouristic valours of the Klyuchevskaya group of volcanoes in the Northern Kamchatka. The relationships are presented between the Kamchatka and the recent boundaries of crustal plates, then the genesis and the structure are explained of the Koryak-Kamchatka volcanic belt. The geotectonic position of Kamchatka as a part of the “Circumpacific Ring of Fire” enables us to recognize the manifestations of the recent volcanism (shield volcanoes, stratovolcanoes, lava domes, calderas, ignimbrites, lahars, gas and vapour exhalations, native sulphur encrustations). Apart from volcanic activity, the exceptional tourist value of the Northern Kamchatka is the highmountain relief shaped by glaciers, weathering and river erosion.